Positive active material for rechargeable lithium battery, preparing method thereof and rechargeable lithium battery including the same

KR103020683B1Active Publication Date: 2026-09-16SAMSUNG SDI CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020250045699
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-13
Filing Date
2025-04-08
Publication Date
2026-09-16
Estimated Expiration
2042-08-03

Smart Images

  • Figure 112025039661028-PAT00003_ABST
    Figure 112025039661028-PAT00003_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery comprising a lithium nickel-based composite oxide, a secondary particle formed by the aggregation of a plurality of primary particles, and a cobalt coating portion located on the surface of said secondary particle, and a second positive electrode active material comprising a lithium nickel-based composite oxide, a single crystal, and a cobalt coating portion located on the surface of said single crystal, wherein the second positive electrode active material has an uneven surface having unevenness and a flat surface without unevenness, and the BET specific surface area of ​​the positive electrode active material for a lithium secondary battery comprising the first positive electrode active material and the second positive electrode active material is 0.2 m2 / g to 0.6 m2 / g, a method for manufacturing the same, and a lithium secondary battery comprising the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The invention relates to a positive electrode active material for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery containing the same. Background Technology

[0002] Lithium-ion batteries, which offer high energy density and portability, are primarily used as the power source for mobile information terminals such as mobile phones, laptops, and smartphones. Recently, active research is being conducted to utilize high-energy-density lithium-ion batteries as power sources for driving or energy storage in hybrid and electric vehicles.

[0003] Various cathode active materials are being investigated to realize lithium secondary batteries suitable for these applications. Among them, lithium nickel-based oxides, lithium nickel manganese cobalt composite oxides, lithium nickel cobalt aluminum composite oxides, and lithium cobalt oxides are primarily used as cathode active materials. However, these cathode active materials face problems such as structural collapse or cracking due to repeated charge-discharge cycles, which degrades the long-term lifespan of the lithium secondary battery and increases resistance, resulting in unsatisfactory capacity characteristics. Therefore, there is a need to develop new cathode active materials that can secure long-term lifespan characteristics while achieving high capacity and high energy density. The problem to be solved

[0004] The present invention provides a positive electrode active material for a lithium secondary battery with improved lifespan characteristics and safety while achieving high capacity, a method for manufacturing the same, and a lithium secondary battery including the same. means of solving the problem

[0005] In one embodiment, a first positive active material comprising a lithium nickel-based composite oxide, a plurality of primary particles aggregated into secondary particles, and a cobalt coating portion located on the surface of said secondary particles; and a second positive active material comprising a lithium nickel-based composite oxide, a single crystal, and a cobalt coating portion located on the surface of said single crystal, wherein the second positive active material has an uneven surface having irregularities and a flat surface without irregularities, and the BET specific surface area of ​​the positive active material for a lithium secondary battery comprising the first positive active material and the second positive active material is 0.2 m² 2 / g to 0.6 m 2 Provides a positive electrode active material for a lithium secondary battery, with a content of / g.

[0006] In another embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery is provided, comprising: mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide; mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide; and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and performing a third heat treatment.

[0007] In another embodiment, a lithium secondary battery comprising a positive electrode and a negative electrode and an electrolyte is provided, comprising the positive electrode active material. Effects of the invention

[0008] A positive electrode active material for a lithium secondary battery manufactured according to one embodiment and a lithium secondary battery containing the same can achieve high capacity and high energy density while exhibiting excellent charge / discharge efficiency, lifespan characteristics, and safety. Brief explanation of the drawing

[0009] FIG. 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Figure 2 is a scanning electron microscope image of the second positive active material of Example 1. Figure 3 is a scanning electron microscope image of the second positive active material before the third heat treatment after cobalt coating in Example 2. Figure 4 is a scanning electron microscope image of the final second positive electrode active material in Example 2. Figure 5 is a scanning electron microscope image of the second positive active material of Comparative Example 1. Figure 6 is a scanning electron microscope image of the second positive active material of Comparative Example 2. Figure 7 is a photograph showing the mapping of cobalt elements by SEM-EDS (Scanning Electron Microscope - Energy Dispersive Spectroscopy) analysis of the second positive electrode active material according to Example 1. Figure 8 is a photograph of the cobalt element mapped by SEM-EDS analysis of the second cathode active material according to Comparative Example 1. Specific details for implementing the invention

[0010] Specific embodiments are described below in detail so that those skilled in the art can easily implement them. However, the present invention may be implemented in various different forms and is not limited to the embodiments described herein.

[0011] The terms used herein are for describing exemplary embodiments only and are not intended to limit the invention. The singular expression includes the plural expression unless the context clearly indicates otherwise.

[0012] Here, "combinations of these" refers to mixtures of components, laminates, composites, copolymers, alloys, blends, reaction products, etc.

[0013] The terms "include," "equip," or "have" used herein are intended to specify the existence of the implemented features, numbers, steps, components, or combinations thereof, and should be understood as not excluding in advance the existence or addition of one or more other features, numbers, steps, components, or combinations thereof.

[0014] In the drawings, thicknesses have been enlarged to clearly represent various layers and regions, and the same reference numerals have been used for similar parts throughout the specification. When a part such as a layer, film, region, or plate is described as being "on" or "on" another part, this includes not only cases where it is "immediately on" another part, but also cases where there is another part in between. Conversely, when a part is described as being "immediately on" another part, it means that there is no other part in between.

[0015] In addition, the term "layer" here includes not only the shape formed on the entire surface when viewed in a plan view, but also the shape formed on some surfaces.

[0016] In addition, the average particle size can be measured by methods widely known to those skilled in the art, for example, by measuring with a particle size analyzer, or by measuring with transmission electron microscope images or scanning electron microscope images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering and performing data analysis to count the number of particles for each particle size range and then calculating from thereon. Unless otherwise defined, the average particle size may refer to the diameter (D50) of a particle whose cumulative volume in the particle size distribution is 50% by volume.

[0017] positive electrode active material

[0018] In one embodiment, the positive electrode active material comprises a first positive electrode active material comprising a lithium nickel-based composite oxide, which is in the form of a secondary particle formed by the aggregation of a plurality of primary particles, and which includes a cobalt coating portion located on the surface of said secondary particle; and a second positive electrode active material comprising a lithium nickel-based composite oxide, which is in the form of a single crystal, and which includes a cobalt coating portion located on the surface of said single crystal, wherein the second positive electrode active material has an uneven surface having irregularities and a flat surface without irregularities, and the BET specific surface area of ​​the positive electrode active material for a lithium secondary battery comprising the first positive electrode active material and the second positive electrode active material is 0.2 m² 2 / g to 0.6 m 2 A cathode active material for a lithium secondary battery is provided, having a content of 1 / g. This cathode active material can exhibit enhanced lifespan characteristics while achieving high capacity and high energy density.

[0019] First positive active material

[0020] The first positive active material is in the form of polycrystalline and includes secondary particles formed by the aggregation of at least two primary particles.

[0021] A first positive active material according to one embodiment includes a cobalt coating portion located on the surface of the secondary particle. The cobalt coating portion may be located on the entire surface of the secondary particle, or at least a part thereof. By coating the first positive active material with cobalt, structural collapse due to repeated charging and discharging is effectively suppressed, thereby improving room temperature and high temperature lifespan characteristics.

[0022] The above cobalt coating portion comprises a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel, etc. For example, the cobalt-containing compound may be lithium cobalt oxide, etc.

[0023] The content of the cobalt coating portion in the first positive active material may be 0.01 mol% to 7 mol% with respect to the entire first positive active material, for example, 0.01 mol% to 6 mol%, 0.1 mol% to 5 mol%, 0.5 mol% to 4 mol%, 1 mol% to 5 mol%, or 2 mol% to 5 mol%, and may also be 0.01 atomic% to 7 atomic%, 0.1 atomic% to 5 atomic%, or 0.5 atomic% to 4 atomic%. In this case, the lithium secondary battery containing the first positive active material can achieve excellent room temperature and high temperature life characteristics.

[0024] The thickness of the cobalt coating portion in the first positive active material is variable depending on the firing temperature during coating, and depending on the firing temperature, cobalt may penetrate into the active material to be coated and / or doped. Accordingly, the thickness of the cobalt coating layer may be, for example, 1 nm to 2 μm, 1 nm to 1.5 μm, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, the lithium secondary battery containing the first positive active material may exhibit excellent room temperature and high temperature life characteristics.

[0025] The average particle size of the first positive active material, that is, the average particle size of the secondary particles, may be 7 μm to 25 μm. For example, it may be 9 μm to 25 μm, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The average particle size of the secondary particles of the first positive active material may be equal to or larger than the average particle size of the second positive active material of a single crystal, which will be described later. The positive active material according to one embodiment may be in the form of a mixture of the first positive active material, which is polycrystalline and covalent, and the second positive active material, which is a single crystal and small particle, thereby improving the density of the mixture and enabling high capacity and high energy density.

[0026] The first cathode active material is a nickel-based cathode active material and comprises a lithium nickel-based composite oxide (or the first nickel-based oxide). The nickel content in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of transition metals excluding lithium, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. As an example, the nickel content in the lithium nickel-based composite oxide may be higher than the respective content of other metals such as cobalt, manganese, and aluminum. When the nickel content satisfies the above range, the cathode active material can exhibit excellent battery performance while achieving high capacity.

[0027] The first positive active material may specifically include a lithium nickel-based composite oxide represented by the following chemical formula 1.

[0028] [Chemical Formula 1]

[0029] Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2

[0030] In the above Chemical Formula 1, 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, and M 1 and M 2 Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0031] In the above chemical formula 1, 0.4≤x1≤1 and 0≤y1≤0.6 may be 0.5≤x1≤1 and 0≤y1≤0.5, 0.6≤x1≤1 and 0≤y1≤0.4, 0.7≤x1≤1 and 0≤y1≤0.3, 0.8≤x1≤1 and 0≤y1≤0.2, or 0.9≤x1≤1 and 0≤y1≤0.1.

[0032] The first positive active material may include, for example, a lithium nickel-based composite oxide represented by Chemical Formula 2 below.

[0033] [Chemical Formula 2]

[0034] Li a2 Ni x2 Co y2 M 3 1-x2-y2 O2

[0035] In the above chemical formula 2, 0.9≤a2≤1.8, 0.3≤x2<1, 0 <y2≤0.7이고 M 3 It is selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0036] In the above chemical formula 2, 0.3≤x2≤0.99 and 0.01≤y2≤0.7 may be 0.4≤x2≤0.99 and 0.01≤y2≤0.6, or 0.5≤x2≤0.99 and 0.01≤y2≤0.5, or 0.6≤x2≤0.99 and 0.01≤y2≤0.4, or 0.7≤x2≤0.99 and 0.01≤y2≤0.3, or 0.8≤x2≤0.99 and 0.01≤y2≤0.2, or 0.9≤x2≤0.99 and 0.01≤y2≤0.1.

[0037] The first positive active material may include, for example, a compound of Chemical Formula 3 below.

[0038] [Chemical Formula 3]

[0039] Li a3 Ni x3 Co y3 M 4z3 M 5 1-x3-y3-z3 O2

[0040] In the above chemical formula 3, 0.9≤a3≤1.8, 0.3≤x3≤0.98, 0.01≤y3≤0.69, 0.01≤z3≤0.69, and M 4 is selected from Al, Mn, and combinations thereof, and M 5 is selected from B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0041] In the above chemical formula 3, 0.4≤x3≤0.98, 0.01≤y3≤0.59, and 0.01≤z3≤0.59 may be 0.5≤x3≤0.98, 0.01≤y3≤0.49, and 0.01≤z3≤0.49, or 0.6≤x3≤0.98, 0.01≤y3≤0.39, and 0.01≤z3≤0.39, or 0.7≤x3≤0.98, 0.01≤y3≤0.29, and 0.01≤z3≤0.29, or 0.8≤x3≤0.98, 0.01≤y3≤0.19, and 0.01≤z3≤0.19, or 0.9≤x3≤0.98, 0.01≤y3≤0.09, and 0.01≤z3≤0.09 may be possible.

[0042] Second positive active material

[0043] The second positive electrode active material is in the form of a single crystal, which means that it exists alone without grain boundaries within the particle and is composed of a single particle. Morphologically, it may refer to a monolith structure, a single body structure, or a non-aggregated particle existing in an independent phase where the particles are not mutually aggregated, and it may also be described as a single crystal particle. The positive electrode active material according to one embodiment can achieve high capacity and high energy density while exhibiting improved lifespan characteristics by including such a second positive electrode active material.

[0044] The shape of the second positive active material is not particularly limited and can have various shapes such as polyhedron, sphere, ellipse, plate-shaped, rod-shaped, and irregular. The second positive active material of a single crystal according to one embodiment may have a polyhedron structure having two or more faces.

[0045] A second positive active material according to one embodiment includes a cobalt coating portion located on the surface of a single crystal. By coating the second positive active material with cobalt, structural collapse due to repeated charging and discharging is effectively suppressed, thereby improving room temperature and high temperature lifespan characteristics.

[0046] The above cobalt coating portion comprises a cobalt-containing compound. The cobalt-containing compound may be, for example, cobalt oxide, cobalt hydroxide, cobalt carbonate, a composite thereof, or a mixture thereof, and may further include lithium and / or nickel, etc. For example, the cobalt-containing compound may be lithium cobalt oxide, etc.

[0047] In the method for manufacturing a positive electrode active material according to an embodiment to be described below, cobalt coating is not performed individually on the first positive electrode active material and the second positive electrode active material; instead, the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material are mixed together, and then a third heat treatment is performed to perform simultaneous coating (or simultaneous firing). According to this, it is confirmed that cobalt is effectively coated only on a portion of the crystal planes of the second positive electrode active material in a single crystal form, and irregularities occur in this portion. Accordingly, a single crystal particle of the second positive electrode active material contains both an uneven surface with a rough shape due to the formation of specific irregularities, and a flat or smooth surface. This is understood to mean that cobalt is effectively coated only on the crystal planes where lithium ion inflow and outflow occur well, thereby causing irregularities. In such a second positive electrode active material, the surface roughness on specific planes increases, and the specific surface area of ​​the second positive electrode active material and the entire positive electrode active material containing it increases. A lithium secondary battery containing such a positive electrode active material can have improved initial discharge capacity, charge / discharge efficiency, and lifespan characteristics.

[0048] The irregularities on the aforementioned surface may be linear or irregular. Additionally, the surface may be described as having a form in which a cobalt-containing compound is attached in a linear or irregular manner, or as a shape in which a cobalt-containing compound covers the surface of a single crystal in a rough form. This form is distinguished from conventional island-type coatings.

[0049] One single crystal grain of the second positive active material may include a rough surface with high surface roughness and a flat surface with low surface roughness. That is, in the second positive active material, the rough surface has high surface roughness. The surface roughness may be measured using a surface roughness measuring instrument, such as an optical profiler, by using a photograph of the object taken with an atomic force microscope (AFM).

[0050] Maximum surface roughness (R max ; peak-to-peak height; maximum roughness depth) can refer to the vertical distance between the highest peak and the lowest valley within the reference length of the roughness cross-section curve (roughness profile). Average roughness (R a Average roughness, also known as centerline average roughness, refers to the arithmetic mean of the absolute values ​​of the ordinates (length from the centerline to the peak) within the reference length of the roughness profile. Mean squared roughness (R q Root mean square roughness refers to the root mean square (rms) of the longitudinal values ​​within the reference length of the roughness profile. For such surface roughness, refer to the parameter definitions and measurement methods defined in KS B 0601 or ISO 4287 / 1.

[0051] The above-mentioned uneven surface of the second positive active material has a maximum roughness (R max ; peak to peak height) may be 18 nm or more, for example, 20 nm or more, 18 nm to 100 nm, 18 nm to 80 nm, 19 nm to 60 nm, or 20 nm to 40 nm. In this case, the cathode active material for a lithium secondary battery containing the second cathode active material exhibits high energy density and high capacity, and can achieve excellent charge / discharge efficiency and lifespan characteristics.

[0052] The above-mentioned uneven surface of the second positive active material has an average roughness (R a; average roughness) may be 1.9 nm or greater, for example, 2.0 nm or greater, 1.9 nm to 10 nm, 1.9 nm to 8.0 nm, 1.9 nm to 6.0 nm, 1.9 nm to 5.0 nm, or 2.0 nm to 10 nm. In this case, the cathode active material for a lithium secondary battery containing the second cathode active material exhibits high energy density and high capacity, and can achieve excellent charge / discharge efficiency and lifespan characteristics.

[0053] The uneven surface of the second positive active material has a mean square roughness (R q ; root mean square roughness) may be 2.3 nm or greater, for example, 2.4 nm or greater, 2.3 nm to 10 nm, 2.3 nm to 8 nm, 2.3 nm to 6 nm, 2.3 nm to 5 nm, or 2.4 nm to 10 nm. In this case, the cathode active material for a lithium secondary battery containing the second cathode active material exhibits high energy density and high capacity, and can achieve excellent charge / discharge efficiency and lifespan characteristics.

[0054] On the other hand, the flat surface of the second positive active material may exhibit a lower surface roughness than the uneven surface. For example, the flat surface of the second positive active material has a maximum roughness (R max ) may be 15 nm or less, for example, 0.1 nm to 14 nm, or 1 nm to 13 nm. In addition, the flat surface of the second positive active material has an average roughness (R a ) may be 1.8 nm or less, for example, 0.1 nm to 1.8 nm, or 0.5 nm to 1.7 nm. The flat surface of the second positive active material has a square mean roughness (R q ) may be 2.2 nm or less, for example, 0.1 nm to 2.2 nm, or 0.5 nm to 2.1 nm.

[0055] As such, the second positive active material, which includes both uneven and flat surfaces, can achieve high capacity and high energy density, have a stable structure without structural collapse during charging and discharging of the battery, and exhibit excellent lifespan characteristics.

[0056] The content of the cobalt coating portion in the second positive active material may be 0.01 mol% to 10 mol% with respect to the entire second positive active material, for example, 0.05 mol% to 9 mol%, 0.1 mol% to 8 mol%, 0.5 mol% to 7 mol%, or 1 mol% to 6 mol%, and may also be 0.01 atomic% to 10 atomic%, 0.1 atomic% to 8 atomic%, or 0.5 atomic% to 6 atomic%. In this case, the lithium secondary battery containing the second positive active material can achieve excellent room temperature and high temperature life characteristics.

[0057] The proportion of the uneven surface to the total surface area of ​​the second positive active material may be approximately 40% to 80%, for example, 45% to 80%, or 50% to 75%. Additionally, the proportion of the flat surface to the total surface area of ​​the second positive active material may be approximately 20% to 60%, for example, 20% to 55%, or 25% to 50%. By including the uneven surface and the flat surface in these proportions, the second positive active material can achieve high capacity while simultaneously exhibiting high lifespan characteristics.

[0058] The thickness of the cobalt coating portion in the second positive electrode active material may be about 1 nm to 2 μm, and for example, 1 nm to 1 μm, 1 nm to 900 nm, 1 nm to 700 nm, 1 nm to 500 nm, 1 nm to 300 nm, 5 nm to 100 nm, or 5 nm to 50 nm. In this case, the lithium secondary battery containing the second positive electrode active material may exhibit excellent room temperature and high temperature life characteristics.

[0059] Meanwhile, the second cathode active material may have sides with different cobalt content. That is, the second cathode active material may have both sides with high cobalt content and sides with low cobalt content in a single crystal. For example, the cobalt content on the side with high cobalt content may be 30 at% to 70 at% or 35 at% to 65 at% relative to the total transition metal excluding lithium. The cobalt content on the side with low cobalt content may be 1 at% to 30 at% or 3 at% to 25 at% relative to the total transition metal excluding lithium. Additionally, the proportion of the side with high cobalt content in a single crystal may be 20% to 50%, and the proportion of the side with low cobalt content may be 50% to 80%. Such a second cathode active material can improve the capacity characteristics and lifespan characteristics of the battery.

[0060] The average particle size of the second positive active material, that is, the average particle size of the single crystal, may be 0.05 μm to 10 μm, for example, 0.1 μm to 8 μm, 0.1 μm to 7 μm, 0.1 μm to 6 μm, or 0.1 μm to 10 μm, and specifically, 1 μm to 5 μm. The particle size of the second positive active material may be equal to or smaller than that of the first positive active material, and accordingly, the density of the positive active material can be further increased.

[0061] The BET specific surface area of ​​the entire cathode active material including the first cathode active material and the second cathode active material is 0.2 m 2 / g to 0.6 m 2 / g, for example, 0.3 m 2 / g to about 0.5 m 2 / g, 0.3 m 2 / g to about 0.4 m 2 It can be / g. In this case, the positive electrode active material can achieve excellent charge / discharge efficiency and lifespan characteristics.

[0062] The second cathode active material comprises a lithium nickel-based composite oxide (or a second nickel-based oxide) as a nickel-based active material. The nickel content in the lithium nickel-based composite oxide may be 30 mol% or more based on the total amount of transition metals excluding lithium, for example, 40 mol% or more, 50 mol% or more, 60 mol% or more, 70 mol% or more, 80 mol% or more, or 90 mol% or more, and 99.9 mol% or less, or 99 mol% or less. As an example, the nickel content in the lithium nickel-based composite oxide may be higher than the respective content of other metals such as cobalt, manganese, and aluminum. When the nickel content satisfies the above range, the cathode active material can exhibit excellent battery performance while achieving high capacity.

[0063] The second positive active material may include, for example, a lithium nickel-based composite oxide represented by the following chemical formula 11.

[0064] [Chemical Formula 11]

[0065] Li a11 Ni x11 M 11 y11 M 12 1-x11-y11 O2

[0066] In the above chemical formula 11, 0.9≤a11≤1.8, 0.3≤x11≤1, 0≤y11≤0.7, and M 11 and M 12 Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0067] In the above chemical formula 11, 0.4≤x11≤1 and 0≤y11≤0.6 may be 0.5≤x11≤1 and 0≤y11≤0.5, or 0.6≤x11≤1 and 0≤y11≤0.4, or 0.7≤x11≤1 and 0≤y11≤0.3, or 0.8≤x11≤1 and 0≤y11≤0.2, or 0.9≤x11≤1 and 0≤y11≤0.1.

[0068] The second positive active material may include, as an example, a lithium nickel-based composite oxide represented by the following chemical formula 12.

[0069] [Chemical Formula 12]

[0070] Li a12 Ni x12 Co y12 M 13 1-x12-y12 O2

[0071] In the above chemical formula 12, 0.9≤a12≤1.8, 0.3≤x12<1, 0 <y12≤0.7이고 M 13 It is selected from Al, B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0072] In the above chemical formula 12, 0.3≤x12≤0.99 and 0.01≤y12≤0.7 may be 0.4≤x12≤0.99 and 0.01≤y12≤0.6, or 0.5≤x12≤0.99 and 0.01≤y12≤0.5, or 0.6≤x12≤0.99 and 0.01≤y12≤0.4, or 0.7≤x12≤0.99 and 0.01≤y12≤0.3, or 0.8≤x12≤0.99 and 0.01≤y12≤0.2, or 0.9≤x12≤0.99 and 0.01≤y12≤0.1.

[0073] The above second positive active material may include, as a specific example, a lithium nickel cobalt composite oxide represented by the following chemical formula 13.

[0074] [Chemical Formula 13]

[0075] Lia13 Ni x13 Co y13 M 14 z13 M 15 1-x13-y13-z13 O2

[0076] In the above chemical formula 13, 0.9≤a13≤1.8, 0.3≤x13≤0.98, 0.01≤y13≤0.69, 0.01≤z13≤0.69, and M 14 is selected from Al, Mn, and combinations thereof, and M 15 is selected from B, Ba, Ca, Ce, Cr, Cu, F, Fe, Mg, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0077] In the above chemical formula 13, 0.4≤x13≤0.98, 0.01≤y13≤0.59, and 0.01≤z13≤0.59 may be 0.5≤x13≤0.98, 0.01≤y13≤0.49, and 0.01≤z13≤0.49, or 0.6≤x13≤0.98, 0.01≤y13≤0.39, and 0.01≤z13≤0.39, or 0.7≤x13≤0.98, 0.01≤y13≤0.29, and 0.01≤z13≤0.29, or 0.8≤x13≤0.98, 0.01≤y13≤0.19, and 0.01≤z13≤0.19, or 0.9≤x13≤0.98, 0.01≤y13≤0.09, and 0.01≤z13≤0.09.

[0078] In a positive electrode active material according to one embodiment, with respect to the total amount of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material may be included in an amount of 50% to 90% by weight, and the second positive electrode active material may be included in an amount of 10% to 50% by weight. The first positive electrode active material may be included, for example, in an amount of 60% to 90% by weight, or 70% to 90% by weight, and the second positive electrode active material may be included in an amount of 10% to 40% by weight, or 10% to 30% by weight. When the content ratio of the first positive electrode active material and the second positive electrode active material is such, the positive electrode active material containing it can achieve a high capacity, improve composite density, and exhibit a high energy density.

[0079] Method for manufacturing positive electrode active material

[0080] In one embodiment, a method for manufacturing a positive electrode active material for a lithium secondary battery is provided, comprising mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide, mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide, and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and performing a third heat treatment to obtain a final positive electrode active material comprising a first positive electrode active material and a second positive electrode active material.

[0081] Here, the first nickel-based oxide and the first positive active material are in the form of secondary particles formed by the aggregation of a plurality of primary particles, and the second nickel-based oxide and the second positive active material are in the form of a single crystal. The first positive active material can be described as a material in which cobalt is coated on the surface of the first nickel-based oxide, and the second positive active material can be described as a material in which cobalt is coated on the surface of the second nickel-based oxide.

[0082] In one embodiment, instead of individually cobalt coating the first positive active material and the second positive active material, cobalt coating is performed simultaneously on a mixture of the first nickel-based oxide and the second nickel-based oxide. Accordingly, the cobalt-coated single-crystal second positive active material possesses both a rough surface and a smooth flat surface, thereby having high surface roughness and a specific surface area. A positive active material for a lithium secondary battery containing such a second positive active material exhibits a high specific surface area and can achieve excellent capacity and lifespan characteristics.

[0083] The first nickel-based hydroxide and the second nickel-based hydroxide are precursors of the positive electrode active material, and each may independently be a nickel hydroxide or a nickel-based complex hydroxide containing an element other than nickel, a nickel-metal complex hydroxide containing a metal other than nickel, or a nickel-transition metal complex hydroxide containing a transition metal other than nickel.

[0084] For example, the first nickel-based hydroxide and the second nickel-based hydroxide may each be independently represented by the following chemical formula 21.

[0085] [Chemical Formula 21]

[0086] Ni x21 M 21 y21 M 22 1-x21-y21 (OH)2

[0087] In the above chemical formula 21, 0.3≤x21≤1, 0≤y21≤0.7, and M 21 and M 22 Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof.

[0088] The particle size of the first nickel-based hydroxide may be 10 μm to 30 μm, for example, 10 μm to 25 μm, 15 μm to 25 μm, or 10 μm to 20 μm. The particle size of the second nickel-based hydroxide may be 1 μm to 9 μm, for example, 2 μm to 9 μm, 2 μm to 8 μm, or 3 μm to 7 μm.

[0089] The above lithium raw material may be, for example, Li2CO3, LiOH, hydrates thereof, or a combination thereof, as a lithium source for the cathode active material.

[0090] When mixing the first nickel-based hydroxide and the lithium raw material, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.

[0091] The first heat treatment above may be carried out in an oxidizing gas atmosphere, for example, in an oxygen atmosphere or an air atmosphere. In addition, the first heat treatment may be carried out at, for example, 600°C to 900°C or 600°C to 800°C, and may be carried out for, for example, 5 to 20 hours or 5 to 15 hours. The second nickel-based oxide obtained through the first heat treatment may also be referred to as the first lithium nickel-based oxide.

[0092] When mixing the second nickel-based hydroxide and the lithium raw material, the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide may be, for example, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, or 1.0 or more, and may be 1.8 or less, 1.5 or less, 1.2 or less, 1.1 or less, or 1.05 or less.

[0093] The second heat treatment described above may also be carried out in an oxidizing gas atmosphere, for example, in an oxygen atmosphere or an air atmosphere. Additionally, the second heat treatment may be carried out at, for example, 800°C to 1100°C or 900°C to 1000°C, and may be carried out for, for example, 5 to 20 hours or 5 to 15 hours. The second nickel-based oxide obtained through the second heat treatment may also be referred to as the second lithium nickel-based oxide.

[0094] The second nickel-based oxide is in a single-crystal form, and a single-crystal form can be obtained by controlling conditions such as the temperature and time of the second heat treatment, or a single-crystal form can be obtained through various conditions when synthesizing the second nickel-based hydroxide by the co-precipitation method.

[0095] The above method for manufacturing a positive electrode active material for a lithium secondary battery may further include mixing a second nickel-based hydroxide and a lithium raw material, performing a second heat treatment, and then grinding the resulting material, thereby enabling the acquisition of a single-crystal second nickel-based oxide. The grinding may be performed using various grinding devices, such as a jet mill. Here, grinding the resulting material is a process for obtaining a single-crystal active material and is distinct from the crushing of general active materials.

[0096] In the process of mixing the first nickel-based oxide and the second nickel-based oxide, the weight ratio of the first nickel-based oxide to the second nickel-based oxide may be 9:1 to 5:5, for example, 9:1 to 6:4, or 8:2 to 7:3. When the mixing ratio of the first nickel-based oxide and the second nickel-based oxide satisfies the aforementioned range, the manufactured cathode active material may exhibit high capacity and high energy density and high electrode density.

[0097] Next, a cobalt coating is performed by mixing the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material, and then performing a third heat treatment. The cobalt coating can be performed in a dry or wet manner. For example, a dry coating can be performed by mixing the first nickel-based oxide, the second nickel-based oxide, and the cobalt raw material without a solvent and then performing a third heat treatment. Alternatively, the first nickel-based oxide and the second nickel-based oxide can be washed by adding them to a solvent such as distilled water and mixing them, and then a wet coating can be performed by dropping the cobalt raw material and performing a third heat treatment.

[0098] The above cobalt raw material may be, for example, cobalt sulfate, cobalt oxide, cobalt nitrate, etc.

[0099] The above cobalt raw material may be mixed such that when the content of metals excluding lithium in the total cathode active material is 100 molar parts, the cobalt included in the cobalt raw material is 0.01 molar to 7 molar parts, or 0.01 molar to 5 molar parts, or 0.1 molar to 4 molar parts, etc.

[0100] The third heat treatment may be carried out in an oxidizing gas atmosphere, such as an oxygen or air atmosphere. Additionally, the third heat treatment may be carried out, for example, at 650°C to 900°C or 650°C to 800°C. The time for the third heat treatment is variable depending on the heat treatment temperature, but is carried out, for example, for 5 to 30 hours or 10 to 24 hours.

[0101] Afterward, the heat treatment is terminated and the material is cooled to room temperature to manufacture a positive electrode active material for a lithium secondary battery according to the above-described embodiment. The manufactured positive electrode active material is in a state in which a first positive electrode active material comprising secondary particles formed by the aggregation of primary particles and a second positive electrode active material in the form of a single crystal are mixed, and each of the first positive electrode active material and the second positive electrode active material is coated with cobalt, and the second positive electrode active material includes both an uneven surface and a flat surface.

[0102] anode

[0103] A positive electrode for a lithium secondary battery may include a current collector and a positive electrode active material layer located on the current collector. The positive electrode active material layer may include a positive electrode active material and may further include a binder and / or a conductive material.

[0104] The above binder serves to adhere the positive active material particles well to each other and also to adhere the positive active material well to the current collector. Representative examples include polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0105] The content of the binder in the above positive active material layer may be approximately 1% to 5% by weight with respect to the total weight of the positive active material layer.

[0106] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotube; metal-based materials containing copper, nickel, aluminum, silver, etc., in the form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; or conductive materials comprising a mixture thereof.

[0107] The content of the conductive material in the above positive active material layer may be 1% to 5% by weight relative to the total weight of the positive active material layer.

[0108] Aluminum foil may be used as the anode current collector, but is not limited thereto.

[0109] cathode

[0110] A negative electrode for a lithium secondary battery comprises a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material layer comprises a negative electrode active material and may further comprise a binder and / or a conductive material.

[0111] The above-mentioned negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.

[0112] A material capable of reversibly intercalating / deintercalating the above lithium ions may be a carbon-based negative electrode active material, such as crystalline carbon, amorphous carbon, or a combination thereof. Examples of the crystalline carbon include graphite such as amorphous, plate-like, flake-like, spherical, or fibrous natural graphite or artificial graphite, and examples of the amorphous carbon include soft carbon or hard carbon, mesophase pitch carbide, calcined coke, etc.

[0113] As the above lithium metal alloy, an alloy of a metal selected from the group consisting of lithium, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn may be used.

[0114] As a material capable of doping and undoping the above lithium, a Si-based negative electrode active material or a Sn-based negative electrode active material may be used, and the Si-based negative electrode active material may include silicon, a silicon-carbon composite, or SiO₂. xExamples of the above Sn-based negative electrode active materials include (0 < x < 2), Si-Q alloy (where Q is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), Sn, SnO2, Sn-R alloy (where R is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Sn), and at least one of these may be mixed with SiO2. The above elements Q and R may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0115] The silicon-carbon composite may be, for example, a silicon-carbon composite comprising a core containing crystalline carbon and silicon particles and an amorphous carbon coating layer located on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. As the amorphous carbon precursor, coal-based pitch, mesophase pitch, petroleum-based pitch, coal-based oil, petroleum-based heavy oil, or polymer resins such as phenolic resin, furan resin, or polyimide resin may be used. In this case, the silicon content may be 10% to 50% by weight of the total weight of the silicon-carbon composite. Additionally, the content of the crystalline carbon may be 10% to 70% by weight of the total weight of the silicon-carbon composite, and the content of the amorphous carbon may be 20% to 40% by weight of the total weight of the silicon-carbon composite. Furthermore, the thickness of the amorphous carbon coating layer may be 5nm to 100nm. The average particle size (D50) of the silicon particles may be 10 nm to 20 μm. The average particle size (D50) of the silicon particles may preferably be 10 nm to 200 nm. The silicon particles may exist in an oxidized form, wherein the atomic content ratio of Si:O within the silicon particles indicating the degree of oxidation may be 99:1 to 33:67. The silicon particles are SiO x It can be a particle, and in this case, SiO x In this specification, the range of x may be greater than 0 and less than 2. Unless otherwise defined, the average particle size (D50) refers to the diameter of a particle in which the cumulative volume in the particle size distribution is 50 volume%.

[0116] The above Si-based negative electrode active material or Sn-based negative electrode active material may be used in combination with a carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material and the carbon-based negative electrode active material are mixed and used, the mixing ratio may be 1:99 to 90:10 by weight.

[0117] The content of the negative electrode active material in the above negative electrode active material layer may be 95% to 99% by weight with respect to the total weight of the negative electrode active material layer.

[0118] In one embodiment, the negative active material layer further comprises a binder and optionally further comprises a conductive material. The content of the binder in the negative active material layer may be 1% to 5% by weight with respect to the total weight of the negative active material layer. Additionally, when further comprising a conductive material, the negative active material layer may comprise 90% to 98% by weight of the negative active material, 1% to 5% by weight of the binder, and 1% to 5% by weight of the conductive material.

[0119] The above binder serves to effectively bond the negative electrode active material particles to each other and also to effectively bond the negative electrode active material to the current collector. As the binder, a water-insoluble binder, a water-soluble binder, or a combination thereof may be used.

[0120] Examples of the above-mentioned water-insoluble binders include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, an ethylene propylene copolymer, polystyrene, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0121] Examples of the above water-soluble binders include rubber-based binders or polymer resin binders. The rubber-based binder may be selected from styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. The polymer resin binder may be selected from polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, ethylenepropylenediene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.

[0122] When a water-soluble binder is used as the above-mentioned cathode binder, a cellulose-based compound capable of imparting viscosity may be further included. As this cellulose-based compound, one or more types such as carboxymethyl cellulose, hydroxypropylmethyl cellulose, methyl cellulose, or alkali metal salts thereof may be mixed and used. Na, K, or Li may be used as the alkali metal. The content of such a thickener may be 0.1 to 3 parts by weight per 100 parts by weight of the cathode active material.

[0123] The above conductive material is used to impart conductivity to the electrode, and any electronically conductive material that does not cause chemical changes can be used in the battery being constructed. Examples include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotube; metal-based materials in the form of metal powder or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or conductive materials including mixtures thereof.

[0124] The above-mentioned cathode current collector may be selected from the group consisting of copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0125] lithium secondary battery

[0126] Another embodiment provides a lithium secondary battery comprising a positive electrode, a negative electrode, a separator located between the positive electrode and the positive electrode, and an electrolyte.

[0127] FIG. 1 is a schematic diagram illustrating a lithium secondary battery according to one embodiment. Referring to FIG. 1, a lithium secondary battery (100) according to one embodiment comprises a battery cell including a positive electrode (114), a negative electrode (112) positioned opposite to the positive electrode (114), a separator (113) disposed between the positive electrode (114) and the negative electrode (112), and an electrolyte for a lithium secondary battery impregnating the positive electrode (114), the negative electrode (112), and the separator (113); a battery container (120) containing the battery cell; and a sealing member (140) sealing the battery container (120).

[0128] The above electrolyte includes a non-aqueous organic solvent and a lithium salt.

[0129] The above-mentioned non-aqueous organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Carbonate-based, ester-based, ether-based, ketone-based, alcohol-based, or aprotic solvents may be used as non-aqueous organic solvents. As for the above-mentioned carbonate-based solvents, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. may be used. The above ester-based solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methylpropionate, ethylpropionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, etc. The above ether-based solvents may include dibutyl ether, tetraglyme, deglyme, dimethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, etc., and the above ketone-based solvents may include cyclohexanone, etc. In addition, the above alcohol-based solvent may include ethyl alcohol, isopropyl alcohol, etc., and the above aprotic solvent may include nitriles such as R-CN (wherein R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group and may include double bonds, aromatic rings, or ether bonds), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes.

[0130] The above-mentioned non-aqueous organic solvents may be used alone or in a mixture of one or more. When used in a mixture of one or more, the mixing ratio can be appropriately adjusted according to the desired battery performance, which is widely understood by those working in the field.

[0131] In addition, the above carbonate-based solvent may be used by mixing cyclic carbonates and chain carbonates. In this case, when the cyclic carbonates and chain carbonates are mixed in a volume ratio of about 1:1 to about 1:9, the performance of the electrolyte may be excellent.

[0132] The above-mentioned non-aqueous organic solvent may further include an aromatic hydrocarbon organic solvent in addition to the carbonate-based solvent. In this case, the carbonate-based solvent and the aromatic hydrocarbon organic solvent may be mixed in a volume ratio of about 1:1 to about 30:1.

[0133] As the above aromatic hydrocarbon solvent, an aromatic hydrocarbon compound of the following chemical formula I may be used.

[0134] [Chemical Formula I]

[0135]

[0136] In the above chemical formula I, R 4 to R 9 The groups are identical or different and are selected from the group consisting of hydrogen, halogen, alkyl groups having 1 to 10 carbon atoms, haloalkyl groups, and combinations thereof.

[0137] Specific examples of the above aromatic hydrocarbon solvents include benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene. It is selected from the group consisting of 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene, and combinations thereof.

[0138] The above electrolyte may further include vinylene carbonate or an ethylene carbonate-based compound of the following chemical formula II as a life-enhancing additive to improve battery life.

[0139] [Chemical Formula II]

[0140]

[0141] In the above chemical formula II, R 10 and R 11 The groups are identical or different from each other and are selected from the group consisting of hydrogen, halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, and the R 10 and R 11 At least one of the groups is selected from the group consisting of halogen groups, cyano groups, nitro groups, and fluorinated C1 to C5 alkyl groups, provided that R 10 and R11 Not all of them are hydrogen.

[0142] Representative examples of the above-mentioned ethylene-based carbonate compounds include difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, or fluoroethylene carbonate. When using more of these lifespan-enhancing additives, the amount used can be appropriately controlled.

[0143] The above lithium salt is a material that is dissolved in a non-aqueous organic solvent and acts as a source of lithium ions within the battery, enabling the operation of a basic lithium secondary battery and facilitating the movement of lithium ions between the positive and negative electrodes.

[0144] Representative examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide): LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, and LiN(C x F 2x+1 SO2)(C y F 2y+1 One or more selected from the group consisting of SO2)(where x and y are natural numbers, for example, integers from 1 to 20), lithium difluoro(bisoxalato) phosphate, LiCl, LiI, LiB(C2O4)2 (lithium bis(oxalato) borate: LiBOB), and lithium difluoro(oxalato) borate (LiDFOB).

[0145] It is preferable to use a lithium salt concentration within the range of 0.1M to 2.0M. When the lithium salt concentration falls within the above range, the electrolyte has appropriate conductivity and viscosity, so it can exhibit excellent electrolyte performance and lithium ions can move effectively.

[0146] The separator (113), also referred to as a separator membrane, separates the positive electrode (114) and the negative electrode (112) and provides a pathway for the movement of lithium ions; any material commonly used in lithium-ion batteries can be used. That is, a material having low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention capacity can be used. For example, it may be selected from glass fiber, polyester, Teflon, polyethylene, polypropylene, polytetrafluoroethylene, or a combination thereof, and may be in the form of a non-woven fabric or a woven fabric. For example, polyolefin-based polymer separators such as polyethylene and polypropylene are mainly used in lithium-ion batteries, and coated separators containing ceramic components or polymer materials may be used to ensure heat resistance or mechanical strength, and may optionally be used in a single-layer or multi-layer structure.

[0147] Lithium secondary batteries can be classified into lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries depending on the type of separator and electrolyte used, and can be classified into cylindrical, prismatic, coin, and pouch types depending on their shape, and into bulk and thin-film types depending on their size. Since the structure and manufacturing methods of these batteries are widely known in this field, a detailed description is omitted.

[0148] A lithium secondary battery according to one embodiment can be used in electric vehicles (EVs), hybrid vehicles such as plug-in hybrid electric vehicles (PHEVs), and portable electronic devices, as it has high capacity and excellent storage stability, lifespan characteristics, and high rate characteristics at high temperatures.

[0149] Examples and comparative examples of the present invention are described below. The following examples are merely illustrative of the present invention, and the present invention is not limited to the following examples.

[0150] Example 1

[0151] 1. Preparation of the first nickel-based oxide in the form of secondary particles

[0152] First nickel-based hydroxide (Ni) obtained by coprecipitation method 0.95 Co 0.04 Mn 0.01 (OH)2) and LiOH are mixed such that the molar ratio of lithium to the total amount of transition metal is 1.04, and a first heat treatment is performed at approximately 750°C for 15 hours in an oxygen atmosphere to obtain a first nickel-based oxide (LiNi 0.95 Co 0.04 Mn 0.01 O2) is obtained. The average particle size of the obtained first nickel-based oxide is approximately 13.8 μm, and it is in the form of secondary particles formed by the aggregation of primary particles.

[0153] 2. Preparation of Second Nickel-Based Oxide in Single Crystal Form

[0154] [Co-precipitation Process]

[0155] A mixed solution is prepared by dissolving nickel sulfate (NiSO4·6H2O), cobalt sulfate (CoSO4·7H2O), and manganese sulfate (MnSO4·H2O) in distilled water, which serves as the solvent. To form a complex, a diluted solution of ammonia water (NH4OH) and sodium hydroxide (NaOH) are prepared as a precipitating agent. Subsequently, the metal raw material mixed solution, ammonia water, and sodium hydroxide are each introduced into the reactor. Next, the reaction is carried out for approximately 20 hours while stirring. Afterward, the slurry solution in the reactor is filtered, washed with high-purity distilled water, and dried for 24 hours to produce a secondary nickel-based hydroxide (Ni 0.94 Co 0.05 Mn 0.01 (OH)2) powder is obtained. The obtained nickel-based hydroxide powder has an average particle size of approximately 4.0 μm, and a specific surface area of ​​approximately 15 m² as measured by BET. 2 / g is.

[0156] [Oxidation Process]

[0157] The obtained secondary nickel-based hydroxide and LiOH are mixed to satisfy Li / (Ni+Co+Mn) = 1.05, fed into a calcination furnace, and a second heat treatment is performed at 910 °C for 8 hours in an oxygen atmosphere. Subsequently, the product is ground for approximately 30 minutes to separate and disperse it into a plurality of secondary nickel-based oxides having a single-crystal structure. The obtained secondary nickel-based oxides with a single-crystal structure (LiNi 0.94 Co 0.05 Mn 0.01 The average particle size of O2 is about 3.7㎛.

[0158] 3. Cobalt Coating and Preparation of Final Anode Active Material

[0159] A first nickel-based oxide and a second nickel-based oxide are mixed in a weight ratio of 7:3, and the mixture is washed with water in a stirrer with a weight ratio of 1:1 to water and dried at 150°C. To this, 5 molar parts of lithium hydroxide and 2.5 molar parts of cobalt oxide are additionally mixed with 100 molar parts of the transition metal of the nickel-based oxide, and then placed into a calcination furnace. A third heat treatment is then performed at approximately 710°C for 15 hours in an oxygen atmosphere. Afterward, the calcination furnace is cooled to room temperature to obtain a final cathode active material in which the first cathode active material and the second cathode active material are mixed.

[0160] The final positive active material is a mixture of a first positive active material in the form of secondary particles and a second positive active material in the form of a single crystal, each of which is coated with cobalt.

[0161] Figure 2 is a scanning electron microscope image of a particle corresponding to the second positive active material in the final positive active material prepared according to Example 1. Referring to Figure 2, it can be seen that the second positive active material, which is a single crystal, has an uneven surface and a flat surface formed on its surface.

[0162] 4. Manufacture of the anode

[0163] A positive electrode active material slurry is prepared by mixing 95% by weight of the final positive electrode active material, 3% by weight of a polyvinylidene fluoride binder, and 2% by weight of a carbon nanotube conductive material in an N-methylpyrrolidone solvent. The positive electrode active material slurry is applied to an aluminum current collector, dried, and then rolled to prepare a positive electrode.

[0164] 5. Manufacture of lithium secondary batteries

[0165] A coin half-cell is manufactured by using a prepared positive electrode and a lithium metal counter electrode, interposing a separator with a polyethylene polypropylene multilayer structure between them, and injecting an electrolyte solution in which 1.0 M LiPF6 lithium salt is added to a solvent mixed with ethylene carbonate and diethyl carbonate in a 50:50 volume ratio.

[0166] Example 2

[0167] In "3. Preparation of Cobalt Coating and Final Cathode Active Material" of Example 1 above, the cathode active material, cathode, and battery are prepared in the same manner as in Example 1, except that the cobalt coating is performed in a wet manner. The cobalt coating process is as follows. A first nickel-based oxide and a second nickel-based oxide are mixed in a weight ratio of 7:3, added to distilled water, and washed while mixing. Cobalt sulfate (CoSO4) corresponding to 2.5 molar parts per 100 molar parts of the transition metal of the nickel-based oxide is slowly added to perform the cobalt coating. Sodium hydroxide (NaOH) is also slowly added. Subsequently, the resulting product is dried at 150°C for 12 hours. Figure 3 is a scanning electron microscope image of the second nickel-based oxide corresponding to a single crystal among the dried materials, and it can be confirmed that an uneven surface and a flat surface are formed on the surface.

[0168] Next, the dried material is introduced into a kiln, and a third heat treatment is performed at approximately 710°C for 15 hours in an oxygen atmosphere. Afterward, the kiln is cooled to room temperature to obtain a final positive active material in which the first positive active material and the second positive active material are mixed.

[0169] Figure 4 is a scanning electron microscope image of a particle corresponding to the second positive active material in single crystal form from the obtained final positive active material. Referring to Figure 4, it can be seen that an uneven surface and a flat surface are formed on the surface of the second positive active material. The average particle size of the second positive active material is approximately 4 μm.

[0170] Comparative Example 1

[0171] In "3. Preparation of Cobalt Coating and Final Positive Active Material" of Example 1 above, the positive active material and the battery are prepared in the same manner as in Example 1, except that the first nickel-based oxide and the second nickel-based oxide are not mixed and then cobalt coated, and the first nickel-based oxide and the second nickel-based oxide are individually cobalt coated and then mixed.

[0172] The cobalt coating process is as follows. A first nickel-based oxide is mixed with 5 molar parts of lithium hydroxide and 3 molar parts of cobalt oxide for every 100 molar parts of a transition metal, then introduced into a calcination furnace, and a third heat treatment is performed at approximately 700°C for 15 hours in an oxygen atmosphere, and the calcination furnace is cooled to room temperature to obtain a first positive active material. Additionally, a second nickel-based oxide is mixed with 5 molar parts of lithium hydroxide and 3 molar parts of cobalt oxide for every 100 molar parts of a transition metal, then introduced into a calcination furnace, and a third heat treatment is performed at approximately 850°C for 15 hours in an oxygen atmosphere, and the calcination furnace is cooled to room temperature to obtain a second positive active material. The first positive active material coated with cobalt and the second positive active material coated with cobalt are mixed in a weight ratio of 7:3 to prepare a final positive active material according to Comparative Example 1.

[0173] Figure 5 is a scanning electron microscope image of the second positive electrode active material prepared according to Comparative Example 1. Referring to Figure 5, it can be seen that the surface of the second positive electrode active material of Comparative Example 1 is smooth and flat without any irregularities.

[0174] Comparative Example 2

[0175] A positive electrode active material and a battery are prepared in the same manner as in Comparative Example 1, except that the third heat treatment step for the second nickel-based oxide in Comparative Example 1 is carried out at approximately 700°C for 15 hours in an oxygen atmosphere.

[0176] Figure 6 is a scanning electron microscope image of the second positive electrode active material prepared according to Comparative Example 2. Referring to Figure 6, it can be seen that the surface of the second positive electrode active material of Comparative Example 2 is smooth and flat without any irregularities.

[0177] Evaluation Example 1: Evaluation of Surface Roughness of Second Anode Active Material

[0178] For the cathode active materials prepared in Examples 1 and 2 and Comparative Examples 1 and 2, the surface roughness of the second cathode active material is measured using an atomic force microscope (DME UHV AFM; scan speed 0.25 μm / s, non-contact mode range 250 nm x 250 nm). The results are shown in Table 1 below. In Table 1, the unit of each value is nm.

[0179] Example 1 Example 2 Comparative Example 1 Comparative Example 2 uneven surface flat surface uneven surface flat surface Maximum roughness (R max ) 35 12.0 23.8 10 6.7 10.1 Average roughness (R a ) 3.35 1.7 2.0 1.2 0.73 0.99 Mean squared roughness (R q ) 4.5 2.0 2.5 1.8 0.8 1.3

[0180] Evaluation Example 2: Specific Surface Area Evaluation

[0181] The specific surface area of ​​the cathode active materials of Examples 1 and 2 and Comparative Examples 1 and 2 was measured, and the results are shown in Table 2 below. The specific surface area was measured using physical adsorption and chemical adsorption phenomena and the Brunauer-Emmett-Teller (BET) method. That is, after measuring the weight of the prepared active material, nitrogen was adsorbed onto the surface of the active material to measure the amount of adsorbed nitrogen gas, and then the specific surface area was calculated using the BET formula.

[0182] BET specific surface area (m 2 / g) Example 1 0.3856 Example 2 0.3652 Comparative Example 1 0.2575 Comparative Example 2 0.2521

[0183] Referring to Table 2, it can be seen that in the case of Example 1 and Example 2, the total specific surface area of ​​the cathode active material including the first cathode active material and the second cathode active material has increased compared to the comparative examples.

[0184] Evaluation Example 3: Evaluation of surface cobalt content

[0185] Scanning electron microscope-energy dispersive spectral analysis (SEM-EDS) was performed on the surface of the single-crystal second cathode active material prepared in Example 1 and Comparative Example 1 to measure the ratio of cobalt content (at%) to nickel and cobalt content on the surface. FIG. 7 is an SEM-EDS analysis image of the second cathode active material of Example 1, where the cobalt content was measured at positions 1 to 4, and the results are shown in Table 3 below. FIG. 8 is an SEM-EDS analysis image of the second cathode active material of Comparative Example 1, where the cobalt content was measured at positions 5 to 8, and the results are shown in Table 4 below.

[0186] location Co / (Ni+Co)(%) Example 1 #1 19.4 #2 60.2 #3 40.7 #4 52.9

[0187] location Co / (Ni+Co)(%) Comparative Example 1 #5 8.9 #6 15.5 #7 12 #8 8.6

[0188] Referring to FIG. 7 and Table 3, it can be seen that in the case of Example 1, there is a surface with a low cobalt content of 19.4 at% and a surface with a high cobalt content of 40 to 60 at%. Referring to FIG. 8 and Table 4, in the case of Comparative Example 1, in which cobalt coating was performed individually on the first and second cathode active materials, the surface cobalt content is in the range of approximately 8 to 16 at%, and it is confirmed that there is almost no difference between crystal planes. In addition, it can be confirmed that the surface cobalt coating content is in a lower range compared to Example 1.

[0189] Evaluation Example 4: Charge / Discharge Efficiency and Lifestyle Characteristics

[0190] Each of the coin half-cells of Examples 1 and 2 and Comparative Examples 1 and 2 was charged under constant current (0.2 C) and constant voltage (4.25 V, 0.05 C cut-off) conditions to measure the charging capacity, rested for 10 minutes, and discharged under constant current (0.2 C) conditions until it reached 3.0 V to measure the discharge capacity. The ratio of the discharge capacity to the charging capacity is expressed as efficiency. The results are shown in Table 5 below.

[0191] In addition, after the initial charge and discharge, the discharge capacity at 50 cycles was measured by repeating the charge and discharge at 1C at 45℃, and the ratio (%) of the discharge capacity at 50 cycles to the initial discharge capacity is shown in Table 5 as the capacity retention rate, i.e., the life characteristic.

[0192] Charging capacity (mAh / g) Discharge capacity (mAh / g) Efficiency (%) 50-cycle capacity retention rate (%, 45℃) Example 1 238.3 211.6 88.8 95.2 Example 2 238.8 208.5 87.3 96.4 Comparative Example 1 236.2 203.8 86.3 93.5 Comparative Example 2 234.5 200.7 85.6 92.3

[0193] Referring to Table 5 above, it can be seen that in the case of Examples 1 and 2, compared to Comparative Examples 1 and 2 in which the first and second positive active materials were individually coated with cobalt and fired, the discharge capacity increased, the charge-discharge efficiency improved, and the high-temperature life characteristics were also enhanced. When both the first and second positive active materials were coated with cobalt, changes such as an increase in specific surface area occurred because the cobalt was effectively coated only on some surfaces of the single-crystal second positive active material, resulting in an uneven surface. It can be seen that in the case of a battery using such positive active materials, characteristics such as initial discharge capacity, charge-discharge efficiency, and lifespan are improved.

[0194] Although preferred embodiments have been described in detail above, the scope of the present invention is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims are also included within the scope of the present invention. Explanation of the symbols

[0195] 100: Lithium secondary battery 112: Negative electrode 113: Separator 114: Anode 120: Battery container 140: Encapsulation member

Claims

Claim 1 A first positive active material comprising a lithium nickel-based composite oxide, a secondary particle formed by the aggregation of a plurality of primary particles, and a cobalt coating portion located on the surface of the secondary particle; and a second positive active material comprising a lithium nickel-based composite oxide, a single crystal, and a cobalt coating portion located on the surface of the single crystal, wherein the second positive active material has an uneven surface having irregularities and a flat surface without irregularities, and the BET specific surface area of ​​the positive active material for a lithium secondary battery comprising the first positive active material and the second positive active material is 0.2 m² 2 / g to 0.6 m 2 positive electrode active material for lithium secondary batteries, with a content of / g. Claim 2 In claim 1, the uneven surface of the second positive active material has a maximum roughness (R max A positive electrode active material for a lithium secondary battery having a peak-to-peak height of 18 nm or more. Claim 3 In claim 1, the uneven surface of the second positive active material has an average roughness (R a ; average roughness) is 1.9 nm or greater, and mean squared roughness (R q A positive electrode active material for a lithium secondary battery having a root mean square roughness of 2.3 nm or more. Claim 4 In claim 1, the flat surface of the second positive active material has a maximum roughness (R max A positive electrode active material for a lithium secondary battery having a thickness of 15 nm or less. Claim 5 In claim 1, the flat surface of the second positive active material has an average roughness (R a ) is 1.8 nm or less, and the mean squared roughness (R q A positive electrode active material for a lithium secondary battery having a thickness of 2.2 nm or less. Claim 6 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the average particle size of the first positive electrode active material is 7 μm to 25 μm and the average particle size of the second positive electrode active material is 1 μm to 10 μm. Claim 7 A positive electrode active material for a lithium secondary battery according to claim 1, wherein, with respect to the total amount of the first positive electrode active material and the second positive electrode active material, the first positive electrode active material is included in an amount of 50% to 90% by weight and the second positive electrode active material is included in an amount of 10% to 50% by weight. Claim 8 A positive electrode active material for a lithium secondary battery according to claim 1, wherein the first positive electrode active material comprises a lithium nickel-based composite oxide represented by the following Chemical Formula 1, and the second positive electrode active material comprises a lithium nickel-based composite oxide represented by the following Chemical Formula 11: [Chemical Formula 1]Li a1 Ni x1 M 1 y1 M 2 1-x1-y1 O2 In the above Chemical Formula 1, 0.9≤a1≤1.8, 0.3≤x1≤1, 0≤y1≤0.7, and M1 and M2 are each independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof, and [Chemical Formula 11]Li a11 Ni x11 M 11 y11 M 12 1-x11-y11 In the above chemical formula 11, O2, 0.9≤a11≤1.8, 0.3≤x11≤1, 0≤y11≤0.7, and M 11 and M 12 Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof. Claim 9 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 1, comprising: mixing a first nickel-based hydroxide and a lithium raw material and performing a first heat treatment to prepare a first nickel-based oxide in the form of secondary particles in which a plurality of primary particles are aggregated; mixing a second nickel-based hydroxide and a lithium raw material and performing a second heat treatment to prepare a second nickel-based oxide in the form of a single crystal; and mixing the first nickel-based oxide, the second nickel-based oxide, and a cobalt raw material and performing a third heat treatment. Claim 10 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 9, wherein the first nickel-based hydroxide and the second nickel-based hydroxide are each independently represented by the following chemical formula 21: [Chemical Formula 21]Ni x21 M 21 y21 M 22 1-x21-y21 (OH)2 In the above chemical formula 21, 0.3≤x21≤1, 0≤y21≤0.7, and M 21 and M 22 Each is independently selected from Al, B, Ba, Ca, Ce, Co, Cr, Cu, F, Fe, Mg, Mn, Mo, Nb, P, S, Si, Sr, Ti, V, W, Zr and combinations thereof. Claim 11 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 9, wherein mixing the first nickel-based hydroxide and the lithium raw material is such that the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the first nickel-based hydroxide is 0.9 or more and 1.2 or less, and mixing the second nickel-based hydroxide and the lithium raw material is such that the ratio of the number of moles of lithium in the lithium raw material to the number of moles of metal contained in the second nickel-based hydroxide is 0.9 or more and 1.2 or less. Claim 12 A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein, in claim 9, the first heat treatment is carried out for 5 to 20 hours at a temperature range of 600 ℃ to 900 ℃. Claim 13 A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein, in claim 9, the second heat treatment is carried out for 5 to 20 hours at a temperature range of 800 ℃ to 1100 ℃. Claim 14 A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein, in claim 9, preparing the second nickel-based oxide involves mixing the second nickel-based hydroxide and the lithium raw material and grinding the product obtained by the second heat treatment to obtain a single crystal second nickel-based oxide. Claim 15 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 9, wherein mixing the first nickel-based oxide and the second nickel-based oxide is such that the weight ratio of the first nickel-based oxide and the second nickel-based oxide is 9:1 to 5:

5. Claim 16 A method for manufacturing a positive electrode active material for a lithium secondary battery according to claim 9, wherein mixing a first nickel-based oxide, a second nickel-based oxide, and a cobalt raw material is such that when the total content of metals excluding lithium in the first nickel-based oxide and the second nickel-based oxide is 100 molar parts, the cobalt contained in the cobalt raw material is 0.01 molar parts to 7 molar parts. Claim 17 A method for manufacturing a positive electrode active material for a lithium secondary battery, wherein, in claim 9, the third heat treatment is carried out for 5 to 30 hours at a temperature range of 650 ℃ to 900 ℃. Claim 18 A lithium secondary battery comprising a positive electrode, a negative electrode, and an electrolyte, comprising a positive active material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN112750999A

  • Positive electrode active material for all-solid-state lithium ion battery, manufacturing method of positive electrode active material for all-solid-state lithium ion battery, and all-solid-state lithium ion battery

    JP2021022547A

  • Positive active material for lithium secondary battery, preparing method thereof, and lithium secondary battery comprising positive electrode including positive active material

    KR1020190065963A

  • Positive active material for rechargeable lithium battery, method of preparing same and rechargeable lithium battery including same

    KR1020200051101A

  • Lithium metal composite oxide, positive electrode active material for lithium secondary battery, positive electrode, and lithium secondary battery

    KR1020210095149A